Role of pleural fluid-serum protein carbonyl gradient in differentiating exudative and transudative effusions - Ghosh, Raghumoy; Mukherjee, Kheya; Maiti, Saumyajit; Bhattacharjee, Debojyoti; Chowdhuri, Shubho (Asian Journal of Medical Sciences, 2020)
Background: Pleural effusions often cause a diagnostic dilemma. The first step in the evaluation of pleural effusions is the distinction between exudates and transudates. Aims and Objectives: The current study was designed to distinguish these two broad subgroups of pleural effusions, based on the protein carbonyl gradient between pleural fluid and serum. Materials and Methods: Forty-four exudative and thirty-six transudative pleural effusion cases based on clinical findings and evaluation by Light’s criteria were selected. Protein carbonyl was measured by established photometric method using dinitrophenylhydrazine (DNPH) method in pleural fluid and serum of all the cases. Results: Oxidative stress, estimated by the protein carbonyl gradient between pleural fluid and serum, was found to be higher in exudates when compared to transudates. No significant difference was existent between exudates of different aetiology. However, the gradient was higher in exudates from males compared to females. No such difference was found among transudates. Conclusions: Carbonyl stress being a simple easily measurable biochemical parameter, pleural fluid to serum protein carbonyl gradient may serve as a useful tool for differentiating pleural effusions based on pathogenesis.